Analisis Motivasi Kerja Pegawai - Didin Mushlihuddin; Anton Tirta Komara; Boy Suzanto (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
This study aims to analyze employee work motivation. Work motivation analyzed is based on Theory Mc Cleland, which consists of 3 (three) dimensions, namely the need for achievement, the need for affiliation, and the need for power. The research method used is descriptive. The sample used is an employee at a government agency in Bandung Regency. Data analysis techniques using descriptive analysis. The results of the study illustrate that employee motivation is sufficient.